2014
DOI: 10.1128/aem.01454-14
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of a Glycerol-Oxidative Pathway in Lactobacillus panis PM1 for Utilization of Bioethanol Thin Stillage: Potential To Produce Platform Chemicals from Glycerol

Abstract: Lactobacillus panis PM1 has the ability to produce 1,3-propanediol (1,3-PDO) from thin stillage (TS), which is the major waste material after bioethanol production, and is therefore of significance. However, the fact that L. panis PM1 cannot use glycerol as a sole carbon source presents a considerable problem in terms of utilization of this strain in a wide range of industrial applications. Accordingly, L. panis PM1 was genetically engineered to directly utilize TS as a fermentable substrate for the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Overall, UBER accelerates the prototyping of genetic circuits and metabolic pathways in non-model hosts without requiring the characterization or reuse of native host promoters. Several industrially important bacterial strains, such as Bacillus , Pseudomonas , Clostridium and Lactobacillus , lack the well-characterized collection of promoters found in E. coli , although modifying their metabolism may be particularly advantageous to overproducing a desired chemical or natural product 8 60 61 62 63 64 65 . Decoupling the host's metabolism from its gene regulation is necessary when engineering metabolic pathways to overproduce a desired product, while still relying on the host's biosynthesis of essential cofactors and metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, UBER accelerates the prototyping of genetic circuits and metabolic pathways in non-model hosts without requiring the characterization or reuse of native host promoters. Several industrially important bacterial strains, such as Bacillus , Pseudomonas , Clostridium and Lactobacillus , lack the well-characterized collection of promoters found in E. coli , although modifying their metabolism may be particularly advantageous to overproducing a desired chemical or natural product 8 60 61 62 63 64 65 . Decoupling the host's metabolism from its gene regulation is necessary when engineering metabolic pathways to overproduce a desired product, while still relying on the host's biosynthesis of essential cofactors and metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…S1 ). Previously, the poor growth on glycerol of some bacteria was also reported, and it was suggested that this glycerol utilization pathway might be toxic for cells due to unbalanced redox power (Kang et al., 2014 ), allosteric inhibition (Applebee et al., 2011 , Zhan et al., 2018 ) or intermediate toxicity (Rittmann et al., 2008 ). In E. coli , the glpFK operon is tightly controlled by the Glp repressor, which is not present in M. alcaliphilum 20Z, and expression of two‐gene cluster glpFK may not be the main reason for poor growth on glycerol in this engineered strain (Weissenborn et al., 1992 ).…”
Section: Resultsmentioning
confidence: 99%
“…The biorefining process uses predominant endemic microorganisms, lactobacilli, especially Lactobacillus panis PM1B. Utilization of glucose by L. panis PM1B produces CO 2 gas, as stated by Kang, Korber, and Tanaka (). In addition, lactobacilli could produce exopolysaccharides (EPS), which may be responsible for particle coagulation in G‐TS and floatation in the fermentation medium, producing clarified liquid and a slurry (Ratanapariyanuch, Shim, Emami, & Reaney, ).…”
Section: Biorefinery Processmentioning
confidence: 95%